2015
DOI: 10.1007/s10522-015-9591-y
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster mitochondrial Hsp22: a role in resistance to oxidative stress, aging and the mitochondrial unfolding protein response

Abstract: Aging is characterized by the accumulation of dysfunctional mitochondria. Since these organelles are involved in many important cellular processes, different mechanisms exist to maintain their integrity. Among them is the mitochondrial unfolding protein response, which triggers the expression of a set of proteins aimed at re-establishing mitochondrial homeostasis. The induction of mitochondrial chaperones expression, particularly of Hsp60 and Hsp70, is a hallmark of this pathway. In Drosophila melanogaster, Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 92 publications
(159 reference statements)
1
24
0
Order By: Relevance
“…Tat-HSP22 protein significantly prevented mitochondrial dysfunction and inhibited the release of cytochrome c from mitochondria to cytosol as well as inhibited cell death via regulation of the expression of the apoptotic proteins Bax, Bcl-2, and active caspase-3. Corroborating our results, other studies have demonstrated that overexpression of HSP22 protein increase resistance to oxidative stress and prevents mitochondrial dysfunction by reducing ROS production during the aging process of flies [14]. Also, overexpression of HSP22 protein inhibits the mitochondria dependent apoptosis through regulation of pro-apoptotic and anti-apoptotic proteins expression in myocardial infarction [41].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Tat-HSP22 protein significantly prevented mitochondrial dysfunction and inhibited the release of cytochrome c from mitochondria to cytosol as well as inhibited cell death via regulation of the expression of the apoptotic proteins Bax, Bcl-2, and active caspase-3. Corroborating our results, other studies have demonstrated that overexpression of HSP22 protein increase resistance to oxidative stress and prevents mitochondrial dysfunction by reducing ROS production during the aging process of flies [14]. Also, overexpression of HSP22 protein inhibits the mitochondria dependent apoptosis through regulation of pro-apoptotic and anti-apoptotic proteins expression in myocardial infarction [41].…”
Section: Discussionsupporting
confidence: 86%
“…The mitochondria play an important role in multiple cellular processes including apoptosis [14]. Mitochondria are known as one of the major sources of reactive oxygen species (ROS) production as a by-product of cellular processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modest reduction in thermotolerance suggests that miR-1002 is one of the key players in the complex stress response network. Many other genes and proteins including heat shock proteins (HSPs) have been found to contribute to stress resistance (Bartelt-Kirbach et al, 2016;Jo et al, 2017;Kawasaki et al, 2016;Morrow et al, 2016;Shukla et al, 2014).…”
Section: Microrna Mir-1002 Is a Part Of The Stress Response Networkmentioning
confidence: 99%
“…Exposure to paraquat leads to the production of ROS (reactive oxygen species) and has often been used in the lab as a proxy to study oxidative stress [31][32][33][34]. Resistance to oxidative stress has been associated with extended lifespan [34][35][36], a trait possibly under selection during invasion of a new area. Furthermore, paraquat has been banned since 2007 in Europe but is still used in the U.S.A and Japan.…”
mentioning
confidence: 99%